Pengaruh Komunikasi Pemasaran, Inovasi Produk, dan Citra Perusahaan terhadap Loyalitas Pelanggan Dua Coffee - Lestari, Hani; Putra, Suadi Sapta; Digdowiseiso, Kumba (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This research aims to analyze the factors influencing customer loyalty at Dua Coffee Cipete, focusing on marketing communication, product innovation, and corporate image. The research methodology employs a survey approach, collecting data through the distribution of questionnaires to Dua Coffee Cipete customers. Probability sampling is utilized, with the technique of simple random sampling to select 96 respondents based on the formula recommended by Wiliam. Data analysis is conducted using hypothesis testing to identify the influence of independent variables on the dependent variable, namely customer loyalty. Hypothesis testing is performed partially to evaluate the contribution of each independent variable to customer loyalty, with significant effects assessed through a comparison of the t-value with a significance level of α = 0.05. The findings of this research are expected to contribute to the understanding of factors affecting customer loyalty in the coffee industry, particularly at Dua Coffee Cipete. The analysis results indicate that marketing communication has a positive and significant impact on customer loyalty, while product innovation has a negative yet insignificant influence on customer loyalty. Meanwhile, the corporate image has a positive and significant effect on Dua Coffee customer loyalty. Based on these conclusions, it is recommended that the management of Dua Coffee Cipete maintain and enhance effective marketing communication strategies while paying attention to product innovation aspects that can increase customer satisfaction. This research provides a foundation for strategic decision-making to strengthen Dua Coffee Cipete's position in the coffee market by improving customer loyalty.